2022
DOI: 10.1002/hlca.202100246
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Cyclopentadiene for Diels–Alder Reactions by Visible‐Light Irradiation of Iron Sandwich Complexes

Abstract: Cyclopentadienes readily undergo fast and selective Diels-Alder reactions which can be used for conjugation of biomolecules and polymers. Herein we present a new method for the photochemical generation of cyclopentadienes by the visible light irradiation of the iron complexes [(C 5 H 4 R)Fe(arene)] + . This reaction proceeds at room temperature, in water, and in the presence of potentially interfering amino acids. Free cyclopentadiene is trapped by dienophiles to give the corresponding Diels-Alder adducts in 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…[9][10][11] Cyclopentadiene (herein after referred to as ''Cp'') is one of the most important reactive dienes in the Diels-Alder reaction. [12][13][14][15] Recently, Cp reactions in click chemistry have been reviewed by Levandowski and Raines. 16 About 80 years ago, Mulliken reported that Cp has longer ultraviolet absorption wavelengths in comparison to open-chain dienes.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Cyclopentadiene (herein after referred to as ''Cp'') is one of the most important reactive dienes in the Diels-Alder reaction. [12][13][14][15] Recently, Cp reactions in click chemistry have been reviewed by Levandowski and Raines. 16 About 80 years ago, Mulliken reported that Cp has longer ultraviolet absorption wavelengths in comparison to open-chain dienes.…”
Section: Introductionmentioning
confidence: 99%
“…10 Because of this, [(C 5 H 5 )Fe(arene)] + complexes have been used as photoinitiators for the cationic polymerization of epoxides and other monomers. 11–14 In addition, we have recently reported the application of such complexes for the controlled photochemical release of cyclopentadienes, 15 as well as for the photochemical patterning by salicylate dyes, that coordinate with iron ions. 16,17 However, these complexes have not been used for photochemical gelation before this work.…”
mentioning
confidence: 99%